The co-mingling of bordering dynamics in the San Diego–Tijuana cross-border metropolis. Issue 2 (3rd April 2019) - Herzog, Lawrence A.; Sohn, Christophe
ABSTRACT: The co-mingling of bordering dynamics in the San Diego–Tijuana cross-border metropolis. Territory, Politics, Governance . The focus of this paper is on the processes of 'debordering' and 'rebordering', and more specifically on what occurs when both forces collide and confront their contrasting goals. The hypothesis developed argues that the two bordering dynamics do not merely contest each other, they also interact and co-mingle. A tripartite analytical framework is proposed based on the functional, constructionist and symbolic dimensions of bordering dynamics. The purpose is to generate hypotheses about co-mingling of the two forces that can be tested empirically. The case of San Diego–Tijuana offers a US–Mexico cross-border metropolis as a work in progress, an urbanized region that is constantly changing and reinventing itself through the entanglement of debordering and rebordering, and, ultimately, the nesting of one category inside the other.